2021
DOI: 10.1007/s00259-021-05520-y
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective intra-individual blinded comparison of [18F]PSMA-1007 and [68 Ga]Ga-PSMA-11 PET/CT imaging in patients with confirmed prostate cancer

Abstract: This large prospective intraindividual comparison of [ 18 F]PSMA-1007 PET/CT vs [ 68 Ga]Ga-PSMA-11 PET/CT has demonstrated overall high concordance (92%) for TNM stage in the context of prostate cancer primary staging, biochemical recurrence and evaluation of patients with metastatic disease. Reduced [ 18 F]PSMA-1007 urinary radiotracer excretion improves characterisation of disease adjacent the bladder (prostate or prostate bed following de nitive treatment, including local invasion) and ureters (peri-ureteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 30 publications
(21 reference statements)
4
64
1
Order By: Relevance
“…The imaging data for prostatic lesions were compared with histopathologic prostate biopsy results expressed as GS. Our results showed concordant findings with both tracers, which is in line with other studies comparing 18 F-PSMA and 68 Ga-PSMA in primary staging [ 8 , 9 , 10 ]. Kuten et al reported in a head-to-head comparison that the identification of all intermediate- and high-risk PC lesions was comparable by both methods [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…The imaging data for prostatic lesions were compared with histopathologic prostate biopsy results expressed as GS. Our results showed concordant findings with both tracers, which is in line with other studies comparing 18 F-PSMA and 68 Ga-PSMA in primary staging [ 8 , 9 , 10 ]. Kuten et al reported in a head-to-head comparison that the identification of all intermediate- and high-risk PC lesions was comparable by both methods [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is not feasible to pathologically confirm every disease site due to patient factors, location or small lesion size. However, sufficient evidence now exists to use [ 18 F]PSMA-1007 PET/CT as a standard of reference and a substitute for histopathological validation, as explained in the methods section [ 4 , 13 , 14 , 26 30 ]. Thirdly, a common issue with the [ 18 F]PSMA-1007 radiotracer is focal uptake in non-specific bone lesions (NSBLs) without an underlying CT correlate definite for prostate metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on strong evidence with multiple studies using both [ 18 F]PSMA-1007 PET/CT and [ 68 Ga]Ga-PSMA-11 PET/CT confirming an excellent diagnostic accuracy and high positive predictive value for the detection of metastatic disease with histopathological validation [ 4 , 13 , 14 , 26 29 ]. Additionally, a recent prospective intra-individual comparative study has demonstrated excellent concordance between [ 18 F]PSMA-1007 and [ 68 Ga]Ga-PSMA-11 PET/CT [ 30 , 31 ]. Therefore, we consider [ 18 F]PSMA-1007 PET/CT as an acceptable substitute for histopathological validation based on this extensive literature.…”
Section: Methodsmentioning
confidence: 99%
“…Muehlematter et al could illustrate in a retrospective assessment of 40 consecutive men who performed mpMRI and PSMA PET-MRI followed by a RP due to intermediate- to high-risk PCa a better sensitivity of PSMA-PET/MRI to detect extracapsular extension and infiltration of the seminal vesicle than with mpMRI [ 24 ]. Actually, despite the limited availability of comparative head-to-head studies with [ 18 F]F-PSMA-1007 and [ 68 Ga]Ga-PSMA-11 for prostate tumor staging, several studies have reported that both these tracers can equally identify predominant prostate lesions in patients with intermediate- or high-risk PCa, although the nonurinary excretion of [ 18 F]F-PSMA-1007 may help evaluate lesions near the urinary bladder better than [ 68 Ga]Ga-PSMA-11 [ 25 , 26 , 27 ].…”
Section: Clinical Indications Of Psma Pet Examinations In Prostate Ca...mentioning
confidence: 99%